Pengabdian kepada Masyarakat dengan Pendekatan Edukatif dan Strategi Kolaboratif Pada Situasi Pandemi Covid-19 di Dusun Krajan, Desa Sumbersekar, Kabupaten Malang - Mardhiyah, Ainatul; Fitrianingsih, Avin Ainur (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Covid-19 has been declared a pandemic by WHO since March 11, 2020. The spread of this virus has reached 114 countries including Indonesia. Preventing the spread of Covid-19 is important to tackle this pandemic. Community service UIN Serving Qaryah Thayyibah is participating in socializing ways to prevent Covid-19. The theme of this activity is the socialization of Covid-19 prevention and the practice of making hand sanitizers according to WHO standards. The method used was education by distributing Covid-19 prevention pocket books and direct meetings with PKK cadres in Krajan Hamlet, Sumbersekar Village, Dau District, Malang Regency. The results of this activity were seen from the enthusiasm of the participants during the socialization activities and the practice of making hand sanitizers. It is hoped that from this activity, the people of Krajan Hamlet can better understand how to prevent the spread of Covid-19 and can make hand sanitizers according to WHO standards.